IEO Evaluation Report on the IMF's Approach to Capital Account Liberalization 2005. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2005)
Drawing on evidence from a sample of emerging market economies over the period 1990-2004, this evaluation report reviews the IMF's approach to capital account liberalization and related issues. The evaluation seeks to contribute to transparency by documenting what in practice has been the IMF's approach to these issues and to identify areas where the IMF's instruments and operating methods might be improved, in order to deal with these issues more effectively.